A high energy absorption nanocrystalline magnesium-based composite material and its preparation method and impact-resistant part
By introducing nanoTi powder and RE elements into the magnesium alloy, and using processes such as hot isostatic sintering, solid solution aging treatment and hot extrusion, the partial aggregate distribution of Ti-Zr solid solution and RE elements at the grain boundary is formed, which solves the problem of poor impact resistance of magnesium alloys and achieves high impact resistance of high-energy-absorbing nanocrystalline magnesium-based composite materials.
Patent Information
- Application Number
- CN202311866167.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-12-29
AI Technical Summary
In practical applications, magnesium alloys have poor impact resistance due to insufficient strength and plastic deformation capabilities, especially under high-speed impact loads.
High energy-absorbing nanocrystalline magnesium-based composite materials are used, which include nanoTi powder reinforcement materials and Mg-RE-Zr-based magnesium alloy matrix. Through processes such as hot isostatic sintering, solid solution aging treatment and hot extrusion, the partial aggregate distribution of Ti-Zr solid solution and RE elements at the grain boundary is formed.
The impact absorption and impact absorption capacity of magnesium-based composite materials has been significantly improved. The average grain size is less than 1μm, and the plastic deformation capacity and impact absorption capacity of the material have been significantly improved.
Smart Images

Figure CN117802375B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of magnesium alloys, and in particular to a high-energy-absorbing nanocrystalline magnesium-based composite material, a preparation method thereof, and an impact-resistant component. Background Art
[0002] As the lightest metal material, magnesium alloy has broad application prospects in aerospace, rail transportation, 3C and other fields. However, because magnesium is a close-packed hexagonal crystal structure with typical texture and heterogeneous units, the strength of magnesium alloy is not as good as other metal materials; there are relatively few slip systems that can be activated at room temperature, and it usually shows poor plastic deformation ability. More importantly, magnesium alloy components are inevitably subjected to high-speed impact loads during actual application, such as the front end, body and tail parts of automobiles. Therefore, the impact resistance of structural materials is one of the extremely important performance indicators.
[0003] The higher the material's impact absorption energy, the stronger its ability to resist external impact. At present, the research on the impact deformation of magnesium alloys is mainly focused on Mg-Al-Zn magnesium alloys, whose absorption energy is only 30-60mJ / m 3 Therefore, it is necessary to develop high-strength, high-plasticity and high-energy-absorbing nanocrystalline magnesium alloy materials.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The object of the present invention is to provide a high energy absorption nanocrystalline magnesium-based composite material and a preparation method and an impact-resistant component thereof, so as to solve or improve the above technical problems.
[0006] This application can be implemented as follows:
[0007] In a first aspect, the present application provides a high energy absorption nanocrystalline magnesium-based composite material, which includes a reinforcing material and a magnesium alloy matrix; wherein the reinforcing material is nano-Ti powder, and the magnesium alloy matrix contains Mg, RE and Zr;
[0008] In the high energy absorption nanocrystalline magnesium-based composite material, the mass percentage of nano Ti powder is 0.5-10%; in the magnesium alloy matrix, the mass percentage of Zr is 0.5-2%, the mass percentage of RE is 2-10%, and RE includes at least one of Gd, Er, Y, Ce and Nd.
[0009] In an optional embodiment, the phase boundaries of the high energy absorption nanocrystalline magnesium-based composite material have a Ti—Zr solid solution, and the RE element is concentrated at the grain boundaries.
[0010] In an optional embodiment, the nano-Ti powder has an average particle size of 10-100 nm; and / or the magnesium alloy matrix is Mg-RE-Zr powder with an average particle size of 10-100 μm.
[0011] In an optional embodiment, the average grain size of the high energy absorption nanocrystalline magnesium-based composite material is less than 1 μm, and / or the impact absorption energy of the high energy absorption nanocrystalline magnesium-based composite material is not less than 100 mJ / m 3 .
[0012] In a second aspect, the present application provides a method for preparing a high energy absorption nanocrystalline magnesium-based composite material as described in any of the aforementioned embodiments, comprising the following steps: hot isostatic pressing, solution aging treatment and hot extrusion of a mixture of a reinforcing material and a magnesium alloy matrix.
[0013] In an optional embodiment, the mixture is obtained by low-energy ball milling of the reinforcing material and the magnesium alloy matrix.
[0014] In an optional embodiment, the conditions for low-energy ball milling include: a rotation speed of 100-150 r / min, a ball-to-material ratio of 10:1-30:1, and a time of 1-2 h.
[0015] In an optional embodiment, before the low-energy ball milling, the method further includes pre-mixing the reinforcement material and the magnesium alloy matrix.
[0016] In an optional embodiment, the premixing speed is 50-100 r / min and the time is 3-5 h.
[0017] In an optional embodiment, the hot isostatic pressing sintering conditions include: a sintering temperature of 400-450° C., a sintering pressure of 100-150 MPa, and a sintering time of 1-2 h.
[0018] In an optional embodiment, the solution aging treatment comprises: subjecting the sintered material obtained by hot isostatic pressing to a solution treatment at 500-550° C. for 5-8 hours, and then to an aging treatment at 200-250° C. for 10-16 hours.
[0019] In an optional embodiment, the extrusion ratio during the hot extrusion process is 15:1-35:1, and the extrusion speed is 0.3-0.8 m / min.
[0020] In an optional embodiment, before hot extrusion, the aging treated sample is kept at 350-400° C. for 30-60 minutes.
[0021] In a third aspect, the present application provides an impact-resistant part, the raw materials for preparing the impact-resistant part include the high energy absorption nanocrystalline magnesium-based composite material of any one of the aforementioned embodiments.
[0022] The beneficial effects of this application include:
[0023] The magnesium-based composite material provided by the present application comprises a reinforcing material and a magnesium alloy matrix, wherein the reinforcing material is nano-Ti powder, and the magnesium alloy matrix contains Mg, RE and Zr. The mass percentage of the nano-Ti powder is 0.5-10%; in the magnesium alloy matrix, the mass percentage of Zr is 0.5-2%, the mass percentage of RE is 2-10%, and RE comprises at least one of Gd, Er, Y, Ce and Nd.
[0024] The magnesium-based composite material with the above characteristics has nano-sized grains, high impact absorption work and strong impact resistance. Its preparation method is simple, easy to operate and suitable for industrial production. The high energy absorption nanocrystalline magnesium-based composite material can be used to prepare impact-resistant parts to improve the impact resistance of impact-resistant parts. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 This is a grain morphology diagram of the high energy absorption nanocrystalline magnesium-based composite material prepared in Example 1 of the present application;
[0027] Figure 2 This is a grain morphology diagram of the high energy absorption nanocrystalline magnesium-based composite material prepared in Example 2 of the present application;
[0028] Figure 3 This is a grain morphology diagram of the high energy absorption nanocrystalline magnesium-based composite material prepared in Example 3 of the present application;
[0029] Figure 4 This is a microstructure morphology of the high energy absorption nanocrystalline magnesium-based composite material prepared in Example 1 of the present application;
[0030] Figure 5 This is a grain morphology diagram of the magnesium-based composite material prepared in Comparative Example 1 of the present application;
[0031] Figure 6 This is a grain morphology diagram of the magnesium-based composite material prepared in Comparative Example 2 of the present application;
[0032] Figure 7 This is a grain morphology diagram of the magnesium-based composite material prepared in Comparative Example 3 of the present application;
[0033] Figure 8This is a grain morphology diagram of the magnesium-based composite material prepared in Comparative Example 4 of the present application. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0035] The high energy absorption nanocrystalline magnesium-based composite material and its preparation method and impact-resistant component provided by the present application are described in detail below.
[0036] The present application proposes a high energy absorption nanocrystalline magnesium-based composite material, which comprises a reinforcing material and a magnesium alloy matrix; wherein the reinforcing material is nano-Ti powder, and the magnesium alloy matrix contains Mg, RE and Zr.
[0037] For reference, in the above-mentioned high energy absorption nanocrystalline magnesium-based composite material, the mass percentage of nano-Ti powder is 0.5-10%, such as 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc., and can also be any other value within the range of 0.5-10%.
[0038] If the mass percentage of nano-Ti powder in the high energy absorption nanocrystalline magnesium-based composite material is higher than 10%, it is not conducive to the formation of infinite solid solution between Ti and Zr at the phase boundary. Excessive nano-Ti powder is easy to agglomerate at the phase boundary, which is not conducive to strengthening the strong interface bonding between the particles and the matrix, and the material plasticity is poor.
[0039] In some embodiments, the high energy absorption nanocrystalline magnesium-based composite material contains a magnesium alloy matrix in addition to the reinforcing material. In other embodiments, the high energy absorption nanocrystalline magnesium-based composite material contains other components as required in addition to the reinforcing material and the magnesium alloy matrix, but the total mass percentage of each component is 100%.
[0040] For reference, the mass percentage of Zr in the magnesium alloy matrix can be 0.5-2%, such as 0.5%, 1%, 1.5% or 2%, etc., or any other value within the range of 0.5-2%. The limiting solubility of Zr in magnesium is 3.8%. Zr is a high melting point metal with a strong solid solution strengthening effect. Zr has the same crystal structure as Mg, and α-Zr can serve as a non-spontaneous nucleation core during crystallization, thereby refining the grains. If the mass percentage of Zr in the magnesium alloy matrix exceeds 2%, in addition to part of the Zr being dissolved into the magnesium alloy matrix and the interface to form a Ti-Zr solid solution, the remaining Zr will precipitate a coarse blocky Mg-Zr second phase inside the grains, and the grain refinement effect will be significantly reduced, and the material will have a large tendency to heat up.
[0041] The mass percentage of RE can be 2-10%, such as 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc., or any other value within the range of 2-10%.
[0042] RE may include, for example, at least one of Gd, Er, Y, Ce, and Nd.
[0043] In some embodiments, the magnesium alloy matrix contains Mg in addition to Zr and RE. In other embodiments, the magnesium alloy matrix contains other elements as required in addition to Zr, RE and Mg, but the sum of the mass percentages of the elements is 100% and the main element is Mg.
[0044] In the present application, the phase boundary of the high energy absorption nanocrystalline magnesium-based composite material has a Ti-Zr solid solution, and the RE element is distributed at the grain boundary.
[0045] By forming a Ti-Zr solid solution at the phase boundary, the formation of a coarse and brittle second phase at the interface can be avoided, the grains can be refined, and the plasticity and impact absorption work of the magnesium-based composite material can be improved. The RE element in the magnesium alloy matrix is concentrated and enriched at the grain boundaries, pinning the grain boundaries and dislocations during deformation, acting as a solute drag, and can also significantly refine the grains.
[0046] It should be emphasized that in conventional magnesium-based composite materials containing RE, the content of RE element usually exceeds 10%. The present application controls the content of RE within 10%, thereby effectively refining the grains while reducing the cost.
[0047] For reference, the average particle size of the nano-Ti powder used in the present application may be 10-100 nm, such as 10 nm, 20 nm, 50 nm, 80 nm or 100 nm, etc., or may be any other value within the range of 10-100 nm.
[0048] The magnesium alloy matrix may be Mg-RE-Zr powder with an average particle size of 10-30 μm. The average particle size of the Mg-RE-Zr powder may be 10 μm, 15 μm, 20 μm, 25 μm or 30 μm, etc., or any other value within the range of 10-30 μm.
[0049] It should be noted that the present application adopts nano-Ti powder with an average particle size of 10-100nm and Mg-RE-Zr powder with an average particle size of 10-100μm. The finer the nano powder, the larger the specific surface area, the more active atoms on the surface, and the easier the surface diffusion. Therefore, the nano-Ti powder with a particle size of 10-100nm is more active and evenly distributed on the surface of the magnesium powder, promoting the formation of Ti-Zr solid solution at the phase boundary. If the average particle size of the nano-Ti powder exceeds 100nm, the activity decreases, and the gaps between particles are large, which is not conducive to the formation of dense composite materials; if the average particle size of the magnesium alloy matrix is less than 10μm, the magnesium alloy powder is more active, and the material is not only easily oxidized during the preparation process, but also there are safety risks, which is not conducive to industrial production.
[0050] In the present application, the average grain size of the high energy absorption nanocrystalline magnesium-based composite material is less than 1 μm. In this range, the grains are fine, resulting in a large number of grain boundaries and greater resistance when dislocations move, which is conducive to enhancing the plastic deformation resistance of the magnesium alloy. In addition, the more grains there are, the more metal plastic deformation can be dispersed inside the grains, and the grain boundaries hinder the expansion of cracks, which can significantly increase the material's impact absorption work.
[0051] In some embodiments, the impact absorption energy of the high energy absorption nanocrystalline magnesium-based composite material is not less than 100 mJ / m 3 .
[0052] In the present application, Ti and Zr segregated at the phase boundary can form an infinite solid solution, and the lattice structure in the solid solution has a certain elasticity and can be deformed freely, so it has good deformation performance, which can greatly improve the plasticity and impact absorption work of the material. At the same time, the atomic size of rare earth elements is relatively large, and the diffusion coefficient in magnesium is small, so they are easily segregated at the grain boundary, solute drag occurs, pinning dislocations and grain boundaries, hindering the migration of dislocations and grain boundaries, and refining the grain size.
[0053] Accordingly, the present application also provides a method for preparing the above-mentioned high energy absorption nanocrystalline magnesium-based composite material, which may include the following steps: hot isostatic pressing sintering, solution aging treatment and hot extrusion of a mixture of a reinforcing material and a magnesium alloy matrix.
[0054] For reference, the above mixture is obtained by low-energy ball milling of the reinforcement material and the magnesium alloy matrix.
[0055] The rotation speed of the low-energy ball mill may be 100-150 r / min, such as 100 r / min, 110 r / min, 120 r / min, 130 r / min, 140 r / min or 150 r / min.
[0056] The ball-to-material ratio of low-energy ball milling can be 10:1-30:1, such as 10:1, 15:1, 20:1, 25:1 or 30:1.
[0057] The time of low-energy ball milling can be 1-2 hours, such as 1 hour, 1.5 hours or 2 hours.
[0058] By performing low-energy ball milling under the above conditions, it is beneficial to evenly distribute Ti on the surface of the magnesium alloy powder. If high-energy ball milling is used, it will promote the mechanical alloying of Ti and magnesium matrix powder to form a second phase. The comprehensive mechanical properties of the composite material prepared after sintering are poor, and the effect of grain refinement to improve the strength and plasticity of the material is not as obvious as the formation of a solid solution between Ti and Zr phase boundaries.
[0059] In some preferred embodiments, before low-energy ball milling, the process further includes pre-mixing the reinforcement material and the magnesium alloy matrix.
[0060] The speed of premixing can be 50-100r / min, such as 50r / min, 60r / min, 70r / min, 80r / min, 90r / min or 100r / min, etc. The time of premixing can be 3-5h, such as 3h, 3.5h, 4h, 4.5h or 5h, etc.
[0061] By premixing the reinforcing material and the magnesium alloy matrix, the reinforcing material can be slightly attached to the surface of the magnesium alloy matrix, which is beneficial for making the Ti powder and the magnesium alloy powder combine more evenly and firmly during the low-energy ball milling process.
[0062] In the present application, the temperature of hot isostatic pressing sintering can be 400-450°C, such as 400°C, 410°C, 420°C, 430°C, 440°C or 450°C, etc. The pressure of hot isostatic pressing sintering can be 100-150MPa, such as 100MPa, 110MPa, 120MPa, 130MPa, 140MPa or 150MPa, etc. The time of hot isostatic pressing sintering can be 1-2h, such as 1h, 1.5h or 2h, etc.
[0063] It should be noted that conventional hot pressing sintering has a high temperature, a long time, a low pressure, poor material density, and grains can easily grow in a high temperature and long time environment, affecting the final mechanical properties of the material. This application adopts the above-mentioned hot isostatic pressing sintering method, and its sintering temperature is lower than that of hot pressing sintering, which can reduce the burning of alloy elements and facilitate the precise control of alloy composition; at the same time, the pressure of the hot isostatic pressing sintering is lower than that of the conventional sintering method, making the prepared material more dense and conducive to obtaining fine grains.
[0064] In the present application, the solution aging treatment may include: subjecting the sintered material obtained by hot isostatic pressing to a solution treatment at 500-550° C. for 5-8 h, and then to an aging treatment at 200-250° C. for 10-16 h.
[0065] The temperature of the solution treatment may be 500° C., 510° C., 520° C., 530° C., 540° C. or 550° C., etc. The time of the solution treatment may be 5 h, 6 h, 7 h or 8 h, etc.
[0066] The temperature of the aging treatment may be 200° C., 210° C., 220° C., 230° C., 240° C., or 250° C., etc. The time of the aging treatment may be 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, or 16 h, etc.
[0067] Through the above-mentioned solid solution aging treatment, on the one hand, the Ti-Zr solid solution can be segregated at the phase boundary, and on the other hand, the RE element can be segregated and enriched at the grain boundary. Without solid solution aging treatment, the RE element will form a coarse blocky Mg-RE phase in the grain or at the grain boundary, affecting the mechanical properties of the composite material.
[0068] In the present application, the extrusion ratio in the hot extrusion process can be 15:1-35:1, such as 15:1, 18:1, 20:1, 22:1, 25:1 or 35:1.
[0069] The extrusion speed may be 0.3-0.8 m / min, such as 0.3 m / min, 0.4 m / min, 0.5 m / min, 0.6 m / min, 0.7 m / min or 0.8 m / min, etc.
[0070] In some embodiments, before hot extrusion, the aging treated sample is kept at 350-400° C. for 30-60 minutes.
[0071] As mentioned above, the preparation method of the high energy absorption nanocrystalline magnesium-based composite material provided in the present application is simple, and a fine-grained magnesium-based composite material can be obtained without repeated heat treatment and multiple severe deformations. The composite material has high strength, plasticity and energy absorption.
[0072] In addition, the present application also provides an impact-resistant component, the raw materials for preparing the impact-resistant component include the above-mentioned high-energy-absorbing nanocrystalline magnesium-based composite material.
[0073] For reference, the impact-resistant parts mentioned above may exemplarily but not limitatively include the front end, body and tail parts of the automobile.
[0074] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0075] Example 1
[0076] This embodiment provides a high energy absorption nanocrystalline magnesium-based composite material, and the preparation method thereof includes:
[0077] S1: Ti powder with an average particle size of 80 nm and Mg-8Gd-1Zr powder with an average particle size of 80 μm were premixed in a double cone mixer at a mass ratio of 2:98 at a speed of 100 r / min for 3 h; then low-energy ball milling was performed with a ball-to-powder ratio of 20:1, a speed of 120 r / min for 2 h to obtain a mixed powder of the reinforcement material and the magnesium alloy matrix.
[0078] S2: The mixed powder is subjected to hot isostatic pressing at a temperature of 450° C., a time of 1 h, and a pressure of 120 MPa to obtain a sintered part.
[0079] S3: The sintered part is solution treated at 530°C for 5 hours, and then aged at 250°C for 10 hours to obtain a solution-aged magnesium-based composite material.
[0080] S4: After the solid solution-aged magnesium-based composite material and the extrusion die are kept at 400°C for 30 minutes, hot extrusion is immediately performed with an extrusion ratio of 30:1 and an extrusion speed of 0.5 m / min, and finally a high energy absorption nanocrystalline magnesium-based composite material is obtained.
[0081] Example 2
[0082] The difference between this embodiment and embodiment 1 is that the magnesium alloy matrix is Mg-8Y-1Zr alloy powder.
[0083] Example 3
[0084] The difference between this embodiment and embodiment 1 is that the magnesium alloy matrix is Mg-4Y-4Gd-1Zr alloy powder.
[0085] Example 4
[0086] This embodiment provides a high energy absorption nanocrystalline magnesium-based composite material, and the preparation method thereof includes:
[0087] S1: Nano-Ti powder with an average particle size of 10 nm and Mg-2Ce-0.5Zr powder with an average particle size of 10 μm were premixed in a double cone mixer at a speed of 50 r / min for 5 h in a mass ratio of 0.5:99.5; then low-energy ball milling was performed with a ball-to-powder ratio of 10:1, a speed of 150 r / min and a time of 2 h to obtain a mixed powder of the reinforcement material and the magnesium alloy matrix.
[0088] S2: The mixed powder is subjected to hot isostatic pressing at a temperature of 400° C., a time of 2 h, and a pressure of 100 MPa to obtain a sintered part.
[0089] S3: The sintered part is solution treated at 500°C for 8 hours, and then aged at 200°C for 16 hours to obtain a solution-aged magnesium-based composite material.
[0090] S4: After the solution-aged magnesium-based composite material and the extrusion die are kept at 350°C for 60 minutes, hot extrusion is immediately performed with an extrusion ratio of 15:1 and an extrusion speed of 0.3 m / min, and finally a high energy absorption nanocrystalline magnesium-based composite material is obtained.
[0091] Example 5
[0092] This embodiment provides a high energy absorption nanocrystalline magnesium-based composite material, and the preparation method thereof includes:
[0093] S1: Nano-Ti powder with an average particle size of 100 nm and Mg-10Nd-2Zr powder with an average particle size of 100 μm were premixed in a double cone mixer at a speed of 100 r / min for 3 hours in a mass ratio of 10:90; then low-energy ball milling was performed with a ball-to-material ratio of 30:1, a speed of 150 r / min and a time of 1.5 to obtain a mixed powder of a reinforcement material and a magnesium alloy matrix.
[0094] S2: The mixed powder is subjected to hot isostatic pressing at a temperature of 420° C., a time of 1.5 h, and a pressure of 150 MPa to obtain a sintered part.
[0095] S3: The sintered part is solution treated at 550°C for 6 hours, and then aged at 220°C for 12 hours to obtain a solution-aged magnesium-based composite material.
[0096] S4: After the solution-aged magnesium-based composite material and the extrusion die are kept at 360°C for 40 minutes, hot extrusion is immediately performed with an extrusion ratio of 35:1 and an extrusion speed of 0.8 m / min, and finally a high energy absorption nanocrystalline magnesium-based composite material is obtained.
[0097] Comparative Example 1
[0098] The difference between this comparative example and Example 1 is that the magnesium alloy matrix does not contain rare earth elements, that is, the magnesium alloy matrix is a non-rare earth AZ31 magnesium alloy matrix (the magnesium alloy matrix contains 3% Al, 1% Zr, and the balance is Mg).
[0099] Comparative Example 2
[0100] The difference between this comparative example and Example 1 is that the sintering process in S2 is hot pressing sintering. Specifically, the hot pressing sintering temperature is 550° C. and the pressure is 30 MPa.
[0101] Comparative Example 3
[0102] The difference between this comparative example and Example 1 is that the nano-Ti powder and Mg-8Gd-1Zr powder in S1 are only pre-mixed and not subjected to low-energy ball milling.
[0103] Comparative Example 4
[0104] The difference between this comparative example and Example 1 is that the solution aging treatment of S3 is not performed, and the sintered part obtained by S2 is directly subjected to the hot extrusion treatment of S4.
[0105] Comparative Example 5
[0106] The difference between this comparative example and Example 1 is that only solution treatment is performed in S3, and no aging treatment is performed.
[0107] Comparative Example 6
[0108] The difference between this comparative example and Example 1 is that in S1, the mass ratio of nano-Ti powder to Mg-8Gd-1Zr powder is 15:85, that is, the content of nano-Ti powder in the composite material is increased.
[0109] Comparative Example 7
[0110] The difference between this comparative example and Example 1 is that in S1, the mass of Zr contained in the magnesium alloy matrix is 3%, that is, the magnesium alloy is Mg-8Gd-3Zr (the content of Zr in the magnesium alloy matrix is increased).
[0111] Comparative Example 8
[0112] The difference between this comparative example and Example 1 is that in S1, the magnesium alloy matrix is Mg-8Ca-1Zr.
[0113] That is, Gd is replaced with Ca.
[0114] Comparative Example 9
[0115] The difference between this comparative example and Example 1 is that in S1, the average particle size of the nano-Ti powder is 1 μm.
[0116] Comparative Example 10
[0117] The difference between this comparative example and Example 1 is that in S1, the average particle size of the Mg-RE-Zr powder is 500 μm.
[0118] Comparative Example 11
[0119] The difference between this comparative example and Example 1 is that in S1, the ball mill is a high-energy ball mill, the ball mill speed is 300 rpm / min, and the ball-to-material ratio is 50:1.
[0120] Test example
[0121] ①, taking Examples 1-3 and Comparative Examples 1-4 as examples, the grain size of the obtained high energy absorption nanocrystalline magnesium-based composite material was tested by EBSD, and the obtained grain morphology was statistically analyzed, and the results are as follows: Figures 1 to 8 As shown in Tables 1 and 2.
[0122] Among them, Table 1 is Figure 4 Spectrum label.
[0123] Table 1 Spectrum labels
[0124] Spectrum Label Spectrum Figure 1 Spectrum Figure 2 Spectrum Figure 3 Spectrum Figure 4 Spectrum Figure 5 Spectrum Figure 6 Spectrum Figure 7 Mg 96.85 89.87 96.10 93.54 94.10 96.79 90.60 Ti - 1.55 - - - - 1.21 G 3.14 8.46 3.89 6.45 5.89 3.20 8.01 Zr 0.01 0.12 0.01 0.01 0.01 0.01 0.18 Total 100.00 100.00 100.00 100.00 100.00 100.00 100.00
[0125] From the comparison of the various figures, it can be seen that the composite material prepared by the method provided in the embodiment of the present application has a grain size that is basically at the nanometer level and contains a large number of grain boundaries, which can effectively hinder the expansion of cracks and greatly improve the impact absorption work of the material.
[0126] ②. The magnesium-based composite materials obtained in Examples 1-5 and Comparative Examples 1-11 were subjected to mechanical property tests, and the results are shown in Table 2.
[0127] Among them, the impact load resistance is tested according to GB / T 2292020 standard, and the room temperature tensile test is tested according to GB / T228.1-2021 standard.
[0128] Table 2 Grain size and mechanical properties test results
[0129]
[0130]
[0131] As can be seen from Table 2, the nano-Ti particles reinforced Mg-RE-Zr magnesium-based composites, after hot isostatic pressing, solution aging and hot extrusion, due to the segregation of RE solid solution atoms at the grain boundaries, can pin the grain boundaries and dislocations, the grain size of the composite material is significantly refined, and the average grain size is less than 1μm; at the same time, Ti-Zr solid solution is formed at the phase boundary, which can improve the plastic deformation ability of the composite material, and the impact absorption energy of the material is greater than 100J / cm2 .
[0132] By comparing Example 1 with Comparative Example 1, it can be seen that the matrix used in Comparative Example 1 is a non-rare earth AZ31 magnesium alloy, and there is neither a solid solution formed between Zr and Ti phase boundaries nor RE element grain boundary segregation and pinning. The composite grain size obtained in this comparative example is larger, the number of grain boundaries is relatively small, and the impact absorption work of the material is lower.
[0133] By comparing Example 1 with Comparative Example 2, it can be seen that, relative to the hot isostatic pressing method, the conventional hot pressing sintering process pressure is relatively low, the sintering temperature is relatively high, the sintering time is relatively long, the prepared material has poor density, and the grains are easily grown under high temperature and long time conditions, affecting the final mechanical properties of the material. By comparing Example 1 with Comparative Example 3, it can be seen that low-energy ball milling can promote further mixing of Ti and magnesium alloy powders and evenly distribute them on the surface of the matrix powder. If low-energy ball milling is not performed, the Ti powder and the magnesium alloy powder are only simply mixed, the problem of nano-Ti agglomeration is still not solved, and the prepared material has poor uniformity.
[0134] By comparing Example 1 with Comparative Examples 4 and 5, it can be seen that without solution aging treatment, the rare earth Gd element precipitates coarse blocky Mg-Gd second phase in the crystal and at the grain boundary, the interface bonding is poor, and there is no segregation and dragging effect of the rare earth element solute. The prepared composite material has a large grain size and low impact absorption work.
[0135] By comparing Example 1 with Comparative Example 6, it can be seen that the content of nano-Ti is too high and it agglomerates at the grain boundaries, the bonding between particles is weak, and the impact absorption energy of the final composite material is not high.
[0136] By comparing Example 1 and Comparative Example 7, it can be seen that the Zr content is too high, the crystal refining effect is weakened, the grain size is large, and a coarse Mg-Zr second phase is precipitated at the interface.
[0137] By comparing Example 1 and Comparative Example 8, it can be seen that the segregation of Ca element at the grain boundary position is not as significant as the solute dragging effect of RE element, and the grain size of the obtained composite material is relatively large.
[0138] By comparing Example 1 and Comparative Example 9, it can be seen that when micron Ti particles are selected for reinforcement, the deformation coordination between the reinforcement particles and the matrix is not as good as that of nanoparticles, and the content of solid solution formed at the interface is less than that of nano-Ti particles, which ultimately leads to larger grain size.
[0139] By comparing Example 1 and Comparative Example 10, it can be seen that when large-sized magnesium alloy powder is selected as the raw material, the gaps between the powders are large and the density of the sintered material is poor.
[0140] By comparing Example 1 and Comparative Example 11, it can be seen that after high-energy ball milling, the nano-Ti powder is embedded in the grooves of the flattened magnesium matrix powder, the dispersion is poor, and the Ti-Zr solid solution cannot be uniformly formed at the phase boundary. At the same time, the rare earth elements are relatively active, and the heat generated by high-energy ball milling causes the temperature to rise rapidly. The rare earth, Ti and Mg powders are easily severely oxidized during the preparation process, and the composite material has a high oxygen content, which is not conducive to the improvement of the final mechanical properties.
[0141] In summary, the magnesium-based composite material provided by the present application has fine grains and strong impact resistance. Its preparation method is simple, easy to operate, and suitable for industrial production. The high energy absorption nanocrystalline magnesium-based composite material can be used to prepare impact-resistant parts to improve the impact resistance of the impact-resistant parts.
[0142] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high energy absorption nanocrystalline magnesium-based composite material, characterized in that: The high energy absorption nanocrystalline magnesium-based composite material comprises a reinforcing material and a magnesium alloy matrix; wherein the reinforcing material is nano-Ti powder, and the magnesium alloy matrix contains Mg, RE and Zr; In the high energy absorption nanocrystalline magnesium-based composite material, the mass percentage of nano-Ti powder is 0.5-10%; in the magnesium alloy matrix, the mass percentage of Zr is 0.5-2%, the mass percentage of RE is 2-10%, and RE includes at least one of Gd, Er, Y, Ce and Nd.
2. The high energy absorption nanocrystalline magnesium-based composite material according to claim 1, characterized in that: The phase boundary of the high energy absorption nanocrystalline magnesium-based composite material has a Ti-Zr solid solution, and the RE element is concentrated at the grain boundary.
3. The high energy absorption nanocrystalline magnesium-based composite material according to claim 1, characterized in that: The nano-Ti powder has an average particle size of 10-100 nm; and / or the magnesium alloy matrix is Mg-RE-Zr powder with an average particle size of 10-100 μm.
4. The high energy absorption nanocrystalline magnesium-based composite material according to any one of claims 1 to 3, characterized in that: The average grain size of the high energy absorption nanocrystalline magnesium-based composite material is less than 1 μm, and / or the impact absorption energy of the high energy absorption nanocrystalline magnesium-based composite material is not less than 100 mJ / m 3 .
5. A method for preparing a high energy absorption nanocrystalline magnesium-based composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: The mixture of the reinforcement material and the magnesium alloy matrix is subjected to hot isostatic pressing, solution aging treatment and hot extrusion.
6. The preparation method according to claim 5, characterized in that: The mixture is obtained by low-energy ball milling of the reinforcement material and the magnesium alloy matrix.
7. The preparation method according to claim 6, characterized in that: The conditions for low-energy ball milling include: a rotation speed of 100-150 r / min, a ball-to-material ratio of 10:1-30:1, and a time of 1-2 h.
8. The preparation method according to claim 6, characterized in that: Before the low-energy ball milling, the method further includes pre-mixing the reinforcing material and the magnesium alloy matrix.
9. The preparation method according to claim 8, characterized in that: The premixing speed is 50-100r / min and the time is 3-5h.
10. The preparation method according to claim 5, characterized in that: The conditions of hot isostatic pressing sintering include: sintering temperature of 400-450°C, sintering pressure of 100-150MPa, and sintering time of 1-2h.
11. The preparation method according to claim 5, characterized in that: The solution aging treatment comprises: subjecting the sintered material obtained by hot isostatic pressing to a solution treatment at 500-550° C. for 5-8 hours, and then to an aging treatment at 200-250° C. for 10-16 hours.
12. The preparation method according to claim 5, characterized in that: The extrusion ratio during the hot extrusion process is 15:1-35:1, and the extrusion speed is 0.3-0.8m / min.
13. The preparation method according to claim 12, characterized in that: Before hot extrusion, the aging treated sample is kept at 350-400°C for 30-60 minutes.
14. An impact-resistant member, characterized in that: The raw material for preparing the impact-resistant part includes the high energy absorption nanocrystalline magnesium-based composite material according to any one of claims 1 to 4.
Citation Information
Patent Citations
In-situ submicron / nanometer particle-reinforced magnesium-matrix composite material and preparation method thereof
CN102061421A
Primary micro / nano titanium carbide and amorphous alloy co-reinforced magnesium alloy composite material and preparation method thereof
CN109439984A